The Influence of City Image Elements on Place Attachments in the Braga Street Area, Bandung City - Achyar Al Rasyid (Global Writing Academica Researching & Publishing, 2022)
The Braga Street Kota Tua area is one of the historical icons in the city of Bandung, which is famous for being a commercial and exclusive center. Old buildings with European-style architecture are the main attraction for tourists both from outside the city and abroad. These characteristics cause the Braga Street Kota Tua area to have an identity so that the city can give a sense of place or a distinct impression to people visiting. This study aims to determine how much influence the city's image has on place attachments in ​​Braga Street, Kota Tua Bandung. This study used a qualitative Mix Method and continued with the quantitative. The results showed that from the elements of the city's image, the five elements, namely landmarks, paths, districts, edges, and nodes, Braga Street in the Kota Tua area of ​​Bandung received a high rating from the respondents, reflecting that Braga Street has been known and has become an iconic place in the city of Bandung. The results also show a place of attachment between individuals around the Braga Street area, both functionally (dependence) and emotionally (identity) simultaneous effect on Place attachment.